2021
DOI: 10.1002/ajmg.a.62515
|View full text |Cite
|
Sign up to set email alerts
|

Robin sequence without cleft palate: Genetic diagnoses and management implications

Abstract: Robin sequence (RS), the triad of micrognathia, glossoptosis, and airway obstruction, is a major cause of respiratory distress and feeding difficulties in neonates. Robin sequence can be associated with other medical or developmental comorbidities in ~50% of cases (“syndromic” RS). As well, RS is variably associated with cleft palate (CP). Previous studies have not investigated differences in clinical characteristics of children with RS based on presence or absence of CP. We retrospectively reviewed 175 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…In this study, anomalies of the cardiovascular system were observed in 18.4% of the cases of PRS with MCA. Similar figures were reported in other studies with a percentage of anomalies of the cardiovascular system varying from 12.1 (Weaver et al, 2022) to 75.0 (Hsieh et al, 1999) with variations for the ventricular septum defects from 24.3 in Indianapolis (Costa et al, 2014) to 50.0 in Strasbourg (this study) and for atrial septum defect from 16.4 in Europe (Santoro et al, 2021) to 40.0 in Denmark (Printzlau & Andersen, 2004). For the anomalies of the central nervous system, the percentages of reported anomalies varied from 6.2 in Denmark (Printzlau & Andersen, 2004) to 19.6 in Indianapolis (Costa et al, 2014) with variation for Arnold Chiari anomaly from 12.1 in Indianapolis (Costa et al, 2014) to 20.0 in Cincinnati (Weaver et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, anomalies of the cardiovascular system were observed in 18.4% of the cases of PRS with MCA. Similar figures were reported in other studies with a percentage of anomalies of the cardiovascular system varying from 12.1 (Weaver et al, 2022) to 75.0 (Hsieh et al, 1999) with variations for the ventricular septum defects from 24.3 in Indianapolis (Costa et al, 2014) to 50.0 in Strasbourg (this study) and for atrial septum defect from 16.4 in Europe (Santoro et al, 2021) to 40.0 in Denmark (Printzlau & Andersen, 2004). For the anomalies of the central nervous system, the percentages of reported anomalies varied from 6.2 in Denmark (Printzlau & Andersen, 2004) to 19.6 in Indianapolis (Costa et al, 2014) with variation for Arnold Chiari anomaly from 12.1 in Indianapolis (Costa et al, 2014) to 20.0 in Cincinnati (Weaver et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Similar figures were reported in other studies with a percentage of anomalies of the cardiovascular system varying from 12.1 (Weaver et al, 2022) to 75.0 (Hsieh et al, 1999) with variations for the ventricular septum defects from 24.3 in Indianapolis (Costa et al, 2014) to 50.0 in Strasbourg (this study) and for atrial septum defect from 16.4 in Europe (Santoro et al, 2021) to 40.0 in Denmark (Printzlau & Andersen, 2004). For the anomalies of the central nervous system, the percentages of reported anomalies varied from 6.2 in Denmark (Printzlau & Andersen, 2004) to 19.6 in Indianapolis (Costa et al, 2014) with variation for Arnold Chiari anomaly from 12.1 in Indianapolis (Costa et al, 2014) to 20.0 in Cincinnati (Weaver et al, 2022). For the musculoskeletal system, the percentages of anomalies reported varied from 11.2 in this series to 34.4 in Europe (Santoro et al, 2021) with variation for syndactyly from 6.8 in Europe (Santoro et al, 2021) to 27.3 in this series, for polydactyly from 2.8 in Europe (Santoro et al, 2021) to 9.1 in Strasbourg (This study) and for limb deficiency from 16.6 in Denmark (Printzlau & Andersen, 2004) to 27.3 in this series, for hypospadias from 5.2 in Europe (Santoro et al, 2021) to 100.0 in Denmark (Printzlau & Andersen, 2004) and in Stanford (Gomez-Ospina &…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The aetiology of RS is not fully understood and is likely to be multifactorial, including genetic disposition and exposure to environmental risk factors during embryogenesis. Proposed exposures include methadone6 18–20 and cigarette smoking 21. Geographical differences in birth prevalence may relate to variation in genetic profiles and environmental exposures, or a ‘latitude gradient’ as has been identified for several other diseases 22–24.…”
Section: Discussionmentioning
confidence: 99%